Prostate Volume is A Predictor of Gleason Score Upgrading after Radical Prostatectomy in Low-Risk Prostate Cancer: A Systematic Review and Meta-analysis - Zou, Qianming; Cao, Jiadong; Chen, Zhiqiang; Wang, Shusheng; Gu, Chiming; Li, Siyi; Xiang, Songtao (Urology Journal, 2024)
Purpose: The prediction of Gleason score (GS) upgrading in patients diagnosed with low-risk prostate cancer is particularly important when opting for active surveillance (AS). Thus, we aimed to explore the association between prostate volume and GS upgrading after radical prostatectomy in low-risk prostate cancer through a meta-analysis. Methods: Multiple databases (Web of Science, MEDLINE, Embase, Scopus, and the Cochrane Library) were searched for eligible studies regarding this issue and reporting sufficient data up to May 2023. Specific search terms such as prostate cancer, radical prostatectomy, and prostate volume were used in our search strategy. Multivariable-adjusted odds ratios (ORs) and associated 95% confidence intervals (CIs) were calculated using random effects models according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. Results: Twenty studies comprising 14,823 patients who underwent radical prostatectomy matched our eligibility criteria. Moreover, GS upgrading between biopsy and surgical pathological specimens occurs in 32.2% (4,771) of cases. The results showed that smaller prostate volume is significantly associated with GS upgrading in patients with low-risk prostate cancer (OR = 1.08, 95% CI = 1.05–1.11; P < 0.001; I-square [I2] = 89.8%) from biopsy to radical prostatectomy after adjusting for confounding factors. Moreover, the results of our subgroup analyses revealed that smaller prostate volume remained a substantial risk factor of GS upgrading in the studies designed as retrospective cohorts and case-control studies performed in America, Italy, Turkey, and China. The findings are robust as indicated by sensitivity and meta-regression analyses. Conclusion: Smaller prostate volume predicts clinically substantial GS upgrading in patients diagnosed with lowrisk prostate cancer after radical prostatectomy. The intriguing findings might be helpful when management options other than surgery are selected based on the inability to recognise the true pathological GS of patients for AS. Further studies focus on risk-stratification and treatment planning for patients with low-grade prostate cancer are still needed to verify our results.